The taxonomic significance of the micro-morphology and phytochemistry of agelanthus dodoneifolius (DC.) Polh. & Wiens in relation to its hosts (2009)
Microscopic, phytochemical and chromatographic studies were carried out on the leaves of the plant Agelanlhits dodimeifolius (DC.) Polh. & Wiens 163 (1992), synonym Tapinanlhus dodoneifolius (DC) Danser 111 (1935), an African mistletoe, occurring on four different host plants. This is to determine the reliability of micro-morphological and phytochemical characters in the taxonomy of this parasite and the phytochemical relationship between the parasite and the hosts. The microscopic examination showed similarities in epidermal characters of the parasite growing on the different hosts studied. They have stomata index of 17.7% to 20.5% on the upper surface while the lower surfaces have stomata index of 16.3% to 19.1%. Phytochemical screening showed presence of various secondary metabolites in the parasite and these varied from host to host, but are intricately related to the phytochemical profile of the host plants. The TLC fingerprinting of A. dodoneifolius leaf extracts also correlated with this variation. This study indicates that A. dodoneifolius present on different hosts might have similar micro-morphological but different chemical characteristics. Therefore, chemical characters might be useful in delineating parasitic taxa in isolation of the host. This will, however, not lead to any good taxonomic conclusion except these chemical characters are supported by characters from other systematic lines of evidence. Meanwhile, such chemical variation might justify the consideration of the parasite on a particular host in the treatment of certain disease(s) by Traditional Medicine Practitioners (TMPs).